Cyber-Physical Systems for Industrial Automation: A Multidisciplinary Approach to Optimization - Dr. S. Shalini; Dr. S. Uma; Banupriya C B; Arun M.V; Ajay K (The Bioscan, 2025)
This writing investigates multiple fields of CPS in industrial automation through analysis of sensor technologies along with data analytics and artificial intelligence methods in combination with networked control systems. The paper examines recent developments and obstacles before presenting an optimization system which boosts operational effectiveness while cutting down system interruptions and keeping systems safe. The research demonstrates that process methodologies built across different disciplines lead to strong flexible operations which automatically organize themselves.